177k views
0 votes
-2(x-3)=4x-6

x-3=-2x+3

3x-3=3

3x=6

x=2

Describe each step Duke made.

User Csvan
by
5.6k points

2 Answers

6 votes

Answer:

duke made a mistake from what I can tell the answer is still x=2

Explanation:

.

User Bilal Rabbi
by
5.4k points
5 votes

Answer: duke made a mistake from what I can tell the answer is still x=2

Explanation:

the correct way is you do the distributive property which he did but it’s supposed to be -2x+6=4x-6 then we combine like terms by adding 2x on both sides to get 6x. Now the equation is 6=6x-6 then we add 6 on both sides to get 12=6x now we divide to get x=2

User Saxophonist
by
5.4k points